2021
DOI: 10.1038/s41598-021-01565-z
|View full text |Cite
|
Sign up to set email alerts
|

Inverse correlation between urethral length and continence before and after native tissue pelvic floor reconstruction

Abstract: Urethral length was evaluated retrospectively in patients with prolapse undergoing anterior native-tissue repair. Effects of age, prolapse stage, defect pattern, urodynamic and clinical stress test findings, and tension-free vaginal tape (TVT) surgery indication were analyzed using Mann–Whitney and Wilcoxon tests and linear and logistic regression. Of 394 patients, 61% had stage II/III and 39% had stage IV prolapse; 90% of defects were central (10% were lateral). Median pre- and postoperative urethral lengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…These symptoms may be due to the urethra being obstructed preoperatively due to the severe prolapse of the organ, which has squeezed and distorted the urethra. Some patients also present with insidious stress incontinence, which gradually becomes apparent after pelvic floor reconstruction due to a change in the urethral angle ( 24 , 25 ). In this study, two new cases of lower urinary tract symptoms of varying degrees were found in the T4 group during the postoperative follow-up period, while no new symptoms were found in the mSSLF group.…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms may be due to the urethra being obstructed preoperatively due to the severe prolapse of the organ, which has squeezed and distorted the urethra. Some patients also present with insidious stress incontinence, which gradually becomes apparent after pelvic floor reconstruction due to a change in the urethral angle ( 24 , 25 ). In this study, two new cases of lower urinary tract symptoms of varying degrees were found in the T4 group during the postoperative follow-up period, while no new symptoms were found in the mSSLF group.…”
Section: Discussionmentioning
confidence: 99%